Fish and Fish Fauna in Narayani River – A Pictorial Survey - Dhakal, Devendra (BMC Journal of Scientific Research, 2018)
The Narayani is the most important typical tropical river of Nepal. It has seven tributaries called the Saptagandaki and drains central Nepal between Langtang and Dhaulagiri himal. The Narayani river drains the edge of Chitwan National Park for down the Trivenighat section of narayani. The temperature of water at river was found ranging between 10.3-27.5°C. The maximum temperature was recorded at station Golaghat, the junction of Narayani and Rapti river in summer and lowest temperature of station was at Benighat, the junction between Trisuli and Budigandaki in winter season. Gandaki river system was found to be the best habitat for fresh water fishes due to its diverse habitat and ecotype. A total of 86 species were recorded from Narayani and Rapti river which belong to 18 family and 46 genera. Economically important fishes found are Tor tor, Tor putitara, Labeo agra, Labeo dero, Wallago attu, Bagarius bagarius, Anguilla bengalensis etc. During the study Tor tor, endangered species and some other nationally threatened species were also recorded from Gandaki river system.